The Fracture Resistance Comparison between Titanium and Zirconia Implant Abutments with and without Ageing: Systematic Review and Meta-Analysis - Marek Chmielewski; Wojciech Dąbrowski; Iwona Ordyniec-Kwaśnica (MDPI AG, 2024)
Implant abutments are essential components of implant prosthetic restorations. The golden standard for abutment material is titanium; however, due to its properties, the esthetic result can be compromised. The most popular esthetic material alternatives are one- and two-piece zirconia. The study aimed to answer the questions of whether zirconia abutments can be used interchangeably with titanium in both anterior and posterior regions and how aging of the abutment affects durability. For this study, an electronic search of MEDLINE (PubMed) and Scopus (Embase) was conducted. The PRISMA guidelines were followed, and a systematic review was registered with PROSPERO. The search revealed 4031 results, of which 17 studies were selected. The strongest material for abutments is titanium, closely followed by two-piece zirconia. One-piece zirconia abutments were the weakest. The cyclic loading above 1,000,000 cycles decreased the fracture resistance of the abutments. Differences in implant diameter, angulation, and restoration affected the fracture strength of all compared materials. The main mode of failure for titanium abutments was screw bending or screw fracture. One-piece zirconia most often presented catastrophic failure with internal hexagon fracture below the implant neck. Two-piece zirconia exhibits a combination of failure modes. Two-piece zirconia abutments may be suitable for use in the posterior region, given their comparable fracture resistance to titanium abutments. Despite the fact that one-piece zirconia is capable of withstanding forces that exceed those exerted during mastication, it is recommended that it be employed primarily in the anterior dentition due to its propensity for unfavorable failure modes.